Islam Kiri dan Ideologi Pancasila: Menyikapi Sila Keadilan Sosial dalam Perspektif Islam - Ana Sopanah; Salma Aulia Riyanti; Mohammad Bagas Rafif; Dimas Meifal Nazry; Muhamad Parhan (FKIP, Universitas Palangka Raya, 2025)
This article explores the relationship between the concept of Leftist Islam (Islam Kiri) and the fifth principle of Pancasila, namely “Social Justice for All Indonesian People,” in an effort to understand how progressive Islamic values can synergize with the national ideology. Leftist Islam, as a school of thought that emphasizes economic justice, advocacy for the oppressed, and critique of capitalism, shares significant intersections with the spirit of social justice embodied in Pancasila. Through normative and historical analysis, this article traces the roots of Leftist Islamic thought and examines how progressive Muslim figures in Indonesia, from the independence era to the present, have sought to interpret Islamic values within the framework of the Pancasila state. The article concludes that the principle of social justice is not only compatible with Islamic teachings, but can also be strengthened through interpretations of Islam that side with the marginalized and the poor. Therefore, the integration of Leftist Islam and Pancasila opens a constructive ideological dialogue for the advancement of social justice in Indonesia.